Patients' Knowledge about Chronic Diseases towards Risk Factors and Warning Signs of Stroke - hassan, Sadiq; Mohammed, widad (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: to assess chronic diseases patients’ knowledge toward stroke risk factors and warning signs, besidesdetermining the relationship between chronic diseases patients’ knowledge and their sociodemographicalcharacteristics.Methodology: A descriptive study was carried out at public medical clinics which has started from December2nd, 2008 to August 8th, 2009. A purposive "non-probability" sample of (300) chronic diseases individuals whowere clients of Public Medical Clinics who have one or more of the following chronic diseases (hypertension,diabetes mellitus, heart diseases, and previous stroke), in Baghdad city. The data were collected through the useof a constructed questionnaire which consists of three parts (1) Sociodemographic data form that consist 7-items(2) Medical data form that consists of 10-items and (3) Main domains of the studied phenomena form consists of3-sections (domains) of definition, warning sings, and risk factors of 62 items, by means of direct interviewtechnique with the chronic diseases patients. Descriptive statistical analysis procedures (frequency, percentage,mean of scores, standard deviation, and relative sufficiency) and inferential statistical analysis procedures(pearson correlation coefficient, contingency coefficient, Chi-square test, and Fisher exact probability test) wereused.Results: The findings of the study indicated that there is a knowledge deficit of chronic diseases patients mainlyin stroke warning signs followed by stroke risk factors. No significant relationship was found between chronicdiseases patients’ knowledge and their gender, employment, while significant relationship was found betweenchronic diseases patients’ knowledge and their age and level of education.Recommendations: The study recommends that an intensive comprehensive, evidence-based obligatory widepopulation-based health education programs are needed to improve awareness of stroke, especially among themost vulnerable groups (chronic diseases patients), eldeely, and less educated persons as well as lay people.